STUDY AND SYNTHESIS OF DIATYCLIC REACTIONS OF 1-TIAIN, 1-THIOCHROMAN AND THEIR PRODUCTS (Scientific journal of the Fergana State University, 2023)
The paper examines the diacylation reaction of 1-thiaine, 1-thiochroman, 2,5-dimethyl-1-thiaine and 6-methyl-1-thiochroman with acetic acid chlorohydride in dichloromethane solution in the presence of the AlCl3 catalyst. As a result of the reaction, it was found that 1-thiaindane, 1-thiochroman and 2-methyl-1-thiainides do not undergo diacylation reactions in the presence of large amounts of catalysts and acylating agents. However, 2,5-dimethyl-1-thian and 6-methyl-1-thiochromans undergo acetic acid chlorohydride to form a large number of acylating agents and catalysts in the diacylation reaction, resulting in the formation  of  2,5-dimethyl-3,6-diacetyl-1-thiaine. detected.